2018
DOI: 10.4314/gmj.v52i3.10
|View full text |Cite
|
Sign up to set email alerts
|

Iodine levels in brands of salt on the markets of Accra, Ghana

Abstract: Introduction: The analysis sought to verify the presence or otherwise and the concentration levels of iodine in the claimed iodated salts on the Ghanaian market.Methods: Eleven (11) most patronized brands of salts, including both local and foreign brands and the raw-pellet salt (crystallized directly from sea water), were obtained from popular shops and markets in Accra. These were analysed both qualitatively and quantitatively by titrimetry, involving the iodate-iodide reaction in acid medium that generates m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 3 publications
1
10
0
Order By: Relevance
“…Similar data were found in a study conducted in the city of Ribeirão Preto, Brazil, which analyzed 295 samples of salt for domestic consumption and showed that iodine concentration was in accordance with the legislation (Alves et al, 2018). In other countries, studies carried out in Morocco (Zahidi et al, 2016) and Ghana (Doku and Bortey, 2018) have shown non-conformity of iodine concentration in iodized salt, according to regulations.…”
Section: Discussionsupporting
confidence: 82%
“…Similar data were found in a study conducted in the city of Ribeirão Preto, Brazil, which analyzed 295 samples of salt for domestic consumption and showed that iodine concentration was in accordance with the legislation (Alves et al, 2018). In other countries, studies carried out in Morocco (Zahidi et al, 2016) and Ghana (Doku and Bortey, 2018) have shown non-conformity of iodine concentration in iodized salt, according to regulations.…”
Section: Discussionsupporting
confidence: 82%
“…The study found that respondents from the northern zone had the lowest level of awareness of mental health law and policy while those from the southern-coastal had the highest level. Challenges with realising the full implementation of the mental health Law (and policy) have been traced to key leadership and governance militating against the development of mental healthcare services in Ghana (56,57). The findings from this current study are consistent with these studies and found that leadership and governance of mental health care at the community level in Ghana remains low.…”
Section: Discussionmentioning
confidence: 99%
“…Cassava mosaic disease (CMD) is very devastating and was first reported in Ghana in the 1930's and government of Ghana (GoG) at that time intervened [16,17]. Government's initiative targeted developing improved varieties tolerant to CMD to salvage cassava production in Ghana.…”
Section: Cassava Breeding Progress and Activitiesmentioning
confidence: 99%